ANALISIS PENGARUH PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPOSIBILITY PADA PERUSAHAAN SEKTOR PERTANIAN - Hutabarat, Metyria Imelda; Lumban Gaol, Manatap Berliana; Zalukhu, Rika Surianto (UNPERBA, 2025)
This research aims to analyze the influence of profitability and company size on disclosure of corporate social responsibility. The data sample was selected using a census method carried out on agricultural sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The sample used was 10 agricultural sector companies. This research is a combination of time series data and cross section. The results of this research show that profitability has positive but not significant effect on disclosure of corporate social responsibility. Company size has positive and significant effect on disclosure of corporate social responsibility. The results of the simultaneous analysis show that profitability and company size have positive and significant effect on disclosure of corporate social responsibility.